2020
DOI: 10.1016/j.heliyon.2020.e04604
|View full text |Cite
|
Sign up to set email alerts
|

Malaria coinfection with Neglected Tropical Diseases (NTDs) in children at Internally Displaced Persons (IDP) camp in Benin City, Nigeria

Abstract: Malaria and Neglected Tropical Diseases (NTDs) are highly endemic in poorer countries of the world. The research investigated the prevalence of parasitic infections among children in Internally Displaced Persons (IDP) camp in Benin City. Faecal, urine and blood specimen were collected from 184 children (100 males and 84 females) aged 6–15. Blood samples were prepared using thick film method and analyzed microscopically. Direct smear technique was employed for faecal sample and sedimentation method to concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
2
4
1
Order By: Relevance
“…The microscopy-based G. duodenalis infection rate detected (29.3%) was in line with those (3–60%) previously reported in Nigerian asymptomatic children [ 24 , 25 , 26 , 27 ]. Other studies conducted in the country have documented infection rates of 0.5–26% in children with diarrhea [ 29 , 30 , 31 , 32 ], of 0.6–25% in HIV+ patients [ 33 , 34 , 35 ], and of 0.6–48% in hospital outpatients [ 36 , 37 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The microscopy-based G. duodenalis infection rate detected (29.3%) was in line with those (3–60%) previously reported in Nigerian asymptomatic children [ 24 , 25 , 26 , 27 ]. Other studies conducted in the country have documented infection rates of 0.5–26% in children with diarrhea [ 29 , 30 , 31 , 32 ], of 0.6–25% in HIV+ patients [ 33 , 34 , 35 ], and of 0.6–48% in hospital outpatients [ 36 , 37 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 90%
“…In Nigeria, the annual number of deaths from diarrheal diseases per 100,000 people decreased from 275.3 in 1990 to 92.5 in 2019 [ 22 ]. Although Giardia infection is not usually associated with mortality, giardiasis seems widely present in the country, affecting both asymptomatic and clinical individuals and livestock ( Table 1 ) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. In addition, very little is currently known on the genetic variability of G. duodenalis circulating in Nigerian human populations.…”
Section: Introductionmentioning
confidence: 99%
“…The finding of STHs prevalence from our study was found lower when compared to studies conducted in Ecuadorian Amazon, Nigeria, and Ethiopia with the prevalence reports of 52.1% [ 20 ], 65% [ 24 ], 46.9% [ 25 ], 84.24% [ 26 ] and 67.3% [ 27 ]. Whereas, our STHs infection prevalence was slightly higher than a study in Jimma 20.9% [ 28 ] and comparable with 32.5% [ 29 ] in Cameroon.…”
Section: Discussioncontrasting
confidence: 90%
“…This is due to the combined loss of red blood cells (erythrocytes) as a result of S. haematobium and Plasmodium infections. This result is also comparable to the findings of Kinung'hi et al 48 in Tanzania, Sumbele et al 7 in Cameroon and Edosomwan et al 49 in Nigeria. We also found a higher prevalence of anaemia in male children than in female children.…”
Section: Discussionsupporting
confidence: 90%
“…We did not discern a significant association between single or multiple parasite infections (S. haematonium and Plasmodium) and malnutrition. Although an association between single and multiple parasite infections and malnutrition have been reported in Kenya and Angola 56,55 , some studies in Nigeria and Tanzania reported no association 57,49 . The lack of association between S. haematobium, Plasmodium sp.…”
Section: Discussionmentioning
confidence: 97%